Rédactions conversationnelles sur papier et sur ordinateur : une étude de cas - Charlotte Dejean (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Until fairly recently, the model of the learner working alone before a computer was prevailing, since the computer was considered as a tool favoring the individualization of the learning process. In the last few years, technologies associated with learning have been considered to be able to facilitate social interactions (teacher-learners and learners-learners). With this in mind, a domain of research concerning Computer Supported Collaborative Learning (CSCL), has been developed, particularly in the English-speaking world. This domain of research is interested in work situations involving two or more people interacting around the same computer, and several people interacting through computers on a networked system (local or Internet). The object of this study relates to the first situation mentioned; we are interested in the interactions between two learners of French as a Foreign Language, writing together a text using the same computer. Thus, these learners are participating in collaborative writing.